Thermodynamic and Kinetic Studies of a-Amylase Catalyzed Reaction in Free and Carrageenan/Chitosan Immobilized State - Sarma, Ritchieraj; Kumar Dolui, Ashoke; Kumar, Atul (Asian Journal of Chemistry, 2014)
The present study deals with the immobilization of a-amylase into carrageenan and chitosan medium and determination of kinetics as well as thermodynamic parameters of both free and immobilized enzyme catalyzed reaction to predict the extent of reaction and the position of equilibrium. At optimized condition, the Km value derived from Lineweaver Burk plot for free enzyme (0.37 % w/v) was lower than the immobilized enzyme (0.48 % w/v for carrageenan and 0.59 % w/v for chitosan immobilized). The free enzyme had an Ea value of 1536 cal/mol compared to those of immobilized enzyme (5463.8 cal/mol for carrageenan and 4736 cal/mol for chitosan immobilized). Computed DS value for free enzyme is more negative than the immobilized enzyme. The increasing value DGº of in immobilized enzyme system indicates that the enzyme-substrate reaction is slower during immobilization. Immobilized enzyme could be reused up to 12 days of storage.